Trends and practices in English language assessment in ASEAN countries: A meta-synthesis study (2021-2025) - Bacus, Remedios; Trasmil, Reynarose (Future Science / FSH-PH Publications, 2025)
Across the linguistically diverse ASEAN (Association of Southeast Asian Nations) member states, English has been acknowledged as the sole official working language. It serves as a unifying medium in business, diplomacy, and education. This study explores emerging assessment practices and methodologies in English language teaching within the regional context over the last five years, considering Kachru’s 3 Concentric Circles Model of the English Language. Using databases and following the PRISMA flow, the selected articles were verified by the three experts in English language teaching. A total of 12 published articles met the eligibility criteria: four from Malaysia, four from the Philippines, and four from Indonesia. With Braun and Clarke’s thematic analysis steps, key factors influencing English language assessment were identified from the validated studies: benchmarking, learner autonomy, ICT integration, upskilling, and preparation for workforce demand. Based on these insights, the meth-synthesis proposes a new framework aimed at addressing the identified challenges. The findings of this study have significant implications for enhancing the quality of English language assessment across ASEAN countries.